DAMPAK MENSTRUASI TERHADAP TINGKAT STRESS DAN KELELAHAN PADA TIM FUTSAL PUTRI - Een Sumarni; Yudi Pratama; M. Pemberdi Intasir (JESA-Jurnal Edukasi Sebelas April, 2022)
The purpose of this study was to determine the impact of menstruation on stress and fatigue in members of the women's futsal team at the Raja Ali Haji Maritime University. The research method uses a quantitative descriptive method with a survey approach. The instrument in this study used a scale by distributing questionnaires. The research sample consisted of 16 women's futsal team at the Raja Ali Haji Maritime University aged 19-21 years who were already menstruating. The sampling technique used was purposive sampling. Analysis of the data using calculations then interpreted in the Criteria table. The results of data analysis showed that menstruation had an impact with moderate criteria on stress and fatigue levels in the women's futsal team at the Raja Ali Haji Maritime University. The impact of menstruation on stress levels is 36% and the impact on fatigue is 60%. Menstruation mostly has an impact on anxiety disorders, intellectual improvement and increased fatigue.